2007
DOI: 10.1177/0899764007300388
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Volunteering for a Nonprofit Membership Association: The Case of ARNOVA

Abstract: Although research indicates that volunteer labor is of significant value to many nonprofit organizations, this value is generally not included in the organization's financial accounting statements. This study discusses the value added to nonprofit membership organizations of the volunteering done by its members. It uses an exploratory case study of the Association for Research on Nonprofits Organizations and Voluntary Action (ARNOVA) to demonstrate how volunteer labor is valued and presented within a social ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…for recruiting, training, screening, managing volunteers) (Freeman, 1997). Three different methods are used to estimate the actual cost or economic value of a volunteer hour: replacement value (Handy & Srinivasan, 2004), investment value and market value (Mook, Handy, Ginieniewiz, & Quarter, 2007). Most studies demonstrated the cost-saving effects of volunteering (Brudney & Duncombe, 1992;Handy & Brudney, 2007;Handy, Mook, & Quarter, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…for recruiting, training, screening, managing volunteers) (Freeman, 1997). Three different methods are used to estimate the actual cost or economic value of a volunteer hour: replacement value (Handy & Srinivasan, 2004), investment value and market value (Mook, Handy, Ginieniewiz, & Quarter, 2007). Most studies demonstrated the cost-saving effects of volunteering (Brudney & Duncombe, 1992;Handy & Brudney, 2007;Handy, Mook, & Quarter, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The identi cation of wage and labor market costs will be possible, but the search for this cost and the amount is challenging and time consuming. Therefore, in studies for this method, the average labor cost of the market is considered to be the best outcome for the voluntary work (19).…”
Section: Methodsmentioning
confidence: 99%
“…The expanded value added statement (EVAS; Mook, Handy, Ginieniewicz, & Quarter, 2007;Mook, Quarter, & Richmond, 2007) provides a useful framework for estimating the value of the broad range of social and economic impacts likely to be associated with volunteer-assisted aging services. Value added is expressed in terms of primary, secondary, and tertiary outputs, and their distribution to a program's stakeholders.…”
Section: Valuing Volunteer Servicesmentioning
confidence: 99%